The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1038/sj.jhh.1001533
|View full text |Cite
|
Sign up to set email alerts
|

Effect of benazepril addition to amlodipine on ankle oedema and subcutaneous tissue pressure in hypertensive patients

Abstract: The aim of this study was to evaluate the effect of benazepril addition to amlodipine antihypertensive treatment on ankle-foot volume (AFV) and pretibial subcutaneous tissue pressure (PSTP), two objective measures of ankle oedema. A total of 32 mild to moderate essential hypertensives (DBP490 and o110 mmHg), aged 30-70 years were studied. After a 4-week placebo period, they were randomized to amlodipine 5 mg o.d. or benazepril 10 mg o.d. or amlodipine 5 mg plus benazepril 10 mg o.d. for 4 weeks, according to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 23 publications
1
18
0
2
Order By: Relevance
“…These findings are similar to previous observations with the ACE-I/CCB combination, both based on spontaneously reported side effects in clinical trials [9][10][11][12] and also on the use of the water displacement technique. 13,14 The mechanisms by Valsartan-amlodipine combination and ankle oedema R Fogari et al which ARB may attenuate the CCB-induced oedema are not clear but possibly resemble those hypothesized for ACE-I. [4][5][6][7][8] Thus, RAAS blockade by both ACE-I and ARB is likely to result in venous capacitance vessels vasodilation with consequent intracapillary pressure normalization and reduced fluid exudation from the intracapillary space into the interstitium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are similar to previous observations with the ACE-I/CCB combination, both based on spontaneously reported side effects in clinical trials [9][10][11][12] and also on the use of the water displacement technique. 13,14 The mechanisms by Valsartan-amlodipine combination and ankle oedema R Fogari et al which ARB may attenuate the CCB-induced oedema are not clear but possibly resemble those hypothesized for ACE-I. [4][5][6][7][8] Thus, RAAS blockade by both ACE-I and ARB is likely to result in venous capacitance vessels vasodilation with consequent intracapillary pressure normalization and reduced fluid exudation from the intracapillary space into the interstitium.…”
Section: Discussionmentioning
confidence: 99%
“…PSTP was measured directly using the balancing open system, described by Lauderer 17 in 1884 and modified by Burch and Sodeman 18 in 1937 and the Malamani device, 19,20 according to a method already described in detail in a previous paper, based on the connection of the pretibial subcutaneous environment to a water manometer. 13 Also in this test, three successive recordings were performed with a good reproducibility (coefficient of variation 0.25%).…”
Section: Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…10,12,22 This theoretical concept is borne out by the results of individual clinical trials that have shown that the incidence of oedema is substantially lower in patients who receive ACEI/ CCB or ARB/CCB combination therapy than in those treated with CCB monotherapy. 6,[15][16][17][18][19][20][21][22] Moreover, a meta-analysis of 82 studies that compared the safety and efficacy of benazepril/amlodipine therapy with that of nine monotherapy regimens concluded that this combination was associated with a lower overall rate of side effects and of side effects that led to withdrawal than either amlodipine or nifedipine monotherapy. Table 1 shows the rates of oedema from eight relevant clinical trials.…”
Section: Mitigation Of Ccb-induced Oedemamentioning
confidence: 99%
“…13,14 The incidence of oedema in CCB-treated patients can be substantially reduced by addition of an inhibitor of the renin-angiotensin system (RAS), that is, an ARB or an angiotensin-converting enzyme inhibitor (ACEI). 5,6,[15][16][17][18][19][20][21][22] This review discusses the pharmacological mechanisms that underlie CCB-induced oedema formation and mitigation of this side effect by ACEIs and ARBs. The data cited in this review were selected for relevance by the author from searches performed using PubMed without specific considerations to patient populations.…”
Section: Introductionmentioning
confidence: 99%